An alternative structured weight management protocol to rapid weight loss in mixed martial arts: a prospective interventional study of pre-competition weight management strategies in professional athletes - Maurício, Clóvis Albuquerque; Artioli, Guilherme Giannini; Gonçalves, Aleksandro Ferreira; Teixeira, Rafael Pereira Azevedo; Vieira, Victor; Brito, Ciro José; Pedreiro, Rodrigo Cunha de Mello; Pérez, Diego Ignacio Valenzuela; Aedo-Muñoz, Esteban Ariel; Pierantozzi, Emanuela; Miarka, Bianca (Frontiers in Nutrition, 2025)
In Mixed Martial Arts (MMA), a combination of combat techniques and physical demands takes center stage. Before competition, many athletes engage in rapid weight loss (RWL) strategies to qualify for lower weight classes, aiming to gain a competitive edge by facing smaller or less physically dominant opponents. This practice is driven by the belief that regaining weight after the official weigh-in enhances strength, power, and resilience during the bout. For MMA athletes, adhering to an evidence-based Weight Management Protocol (WMP), targeting a 10% body weight reduction within 7 days prior to weigh-in, poses a significant challenge. This study evaluated the efficacy and safety of a structured nutritional strategy, including controlled dietary interventions and fluid manipulation, tailored for athletes seeking to lose 10% of body mass, along with evidence-based recommendations for post-weigh-in recovery. We followed 31 professional MMA athletes (28 males, aged 28 ± 4 years), all with established experience in RWL protocols. The study was divided into two phases: pre- and post-RWL assessments. Athletes achieved a mean weight reduction of 7.25 kg (10.6%) within the 7 days leading up to the weigh-in, conducted 8 days before competition. They demonstrated a mean weight regain of 7.5 kg (11.2%) within 30 h post-weigh-in, indicating effective rehydration and recovery. Starting 7 days before the weigh-in, athletes consumed 7 liters of fluids per day, with intake gradually decreasing. On the day before the weigh-in, they consumed only 0.5 liters. Following adherence to the protocol, 67.7% (21 athletes) secured victory in their bouts. This study presents a structured, athlete-centered nutritional approach for RWL, offering a potentially safer and more effective alternative to uncontrolled practices. Future research should explore the physiological, psychological, and performance-related implications of such methods through larger, randomized controlled trials.